Holy hustlers, schism, and prophecy : apostolic reformation in Botswana - Werbner, Richard P. (Anthropology of Christianity, 2011)
This text examines the charismatic Christian reformation presently underway in Botswana's time of AIDS and the moral crisis that divides the church between elders and young apostolic faith healers.